Feasibility and early clinical impact of precision medicine for late-stage cancer patients in a regional public academic hospital. (4th March 2023) - Ladekarl, Morten; Nøhr, Anne Krogh; Sønderkær, Mads; Dahl, Simon Christian; Sunde, Lone; Vestereghem, Charles; Mapendano, Christophe Kamungu; Haslund, Charlotte Aaquist; Pagh, Anja; Carus, Andreas; Lörincz, Tamás; Nowicka-Matus, Kinga; et al.
Abstract: Aim: Our goal was to describe a precision medicine program in a regional academic hospital, characterize features of included patients and present early data on clinical impact. Materials and methods: We prospectively included 163 eligible patients with late-stage cancer of any diagnosis from June 2020 to May 2022 in the Proseq Cancer trial. Molecular profiling of new or fresh frozen tumor biopsies was done by WES and RNAseq with parallel sequencing of non-tumoral DNA as individual reference. Cases were presented at a National Molecular Tumor Board (NMTB) for discussion of targeted treatment. Subsequently, patients were followed for at least 7 months. Results: 80% ( N = 131) of patients had a successful analysis done, disclosing at least one pathogenic or likely pathogenic variant in 96%. A strongly or potentially druggable variant was found in 19% and 73% of patients, respectively. A germline variant was identified in 2.5%. Median time from trial inclusion to NMTB decision was one month. One third ( N = 44) of patients who underwent molecularly profiling were matched with a targeted treatment, however, only 16% were either treated ( N = 16) or are waiting for treatment ( N = 5), deteriorating performance status being the primary cause of failure. A history of cancer among 1st degree relatives, and a diagnosis of lung or prostate cancer correlated with greater chance of targeted treatment being available. The response rate of targeted treatments was 40%, the clinical benefit rate 53%, and the median time on treatment was 3.8 months. 23% of patients presented at NMTB were recommended clinical trial participation, not dependent on biomarkers. Conclusions: Precision medicine in end-stage cancer patients is feasible in a regional academic hospital but should continue within the frame of clinical protocols as few patients benefit. Close collaboration with comprehensive cancer centers ensures expert evaluations and equality in access to early clinical trials and modern treatment.